Vestibular and balance dysfunction in attention deficit hyperactivity disorder and cognitive disengagement syndrome risk groups - Zuhal Koc Apaydın; Emre Soylemez; Nefise Demir (Middle East Current Psychiatry)
Abstract Background In the past, cognitive disengagement syndrome (CDS) and attention deficit hyperactivity disorder (ADHD) were considered similar concepts. However, many differences have recently been identified between the two disorders, and they have been separated from each other. This study aims to investigate balance and vestibular function in individuals at high risk for ADHD and CDS. Materials and methods This study involved 60 college students. Participants were given the Adult ADHD Self-Report Scale and the Adult Concentration Inventory. Using the applied indices, participants with high and low risk for CDS and ADHD were identified. Every participant underwent static posturography, the video head impulse test (vHIT), and cervical vestibular myogenic-evoked potentials (cVEMP). Results People with low and high risk for CDS did not differ in terms of static posturography or cVEMP (p > 0.05). Similarly, no differences were found in ADHD (p > 0.05). While right ear lateral vHIT responses were worse in individuals with high-risk CDS (p > 0.05), bilateral posterior vHIT rates were worse in individuals with high-risk ADHD (p > 0.05). Conclusion The fact that individuals at high risk for CDS and ADHD show different vestibular involvement strengthens the fact that there are different clinical pictures.